Pemanfaatan Perkarangan Rumah untuk Tanaman Hortikultura pada Kelompok Tani Melati Indah Kec Kuantan Hilir Seberang - Yoyon Riono; Elfi Yenny Yusuf (KARYA ABDI, 2021)
This empowerment program is to take advantage of residents' yards in order to optimize land functions with horticultural cultivation techniques. Types of horticultural plants, especially vegetables, are still minimally cultivated by the surrounding community, so that to meet the needs of vegetables by the community they are met by buying vegetable needs. Apart from the problem of the community's inability to meet their vegetable needs, the potential for the house yard or land around the house is underutilized by the community. From some of these problems, it is necessary to carry out activities that can handle problems with the use of empty land. For this reason, an initial understanding of the importance of household agriculture is needed, which is the potential for the residents of Sadang in utilizing their yards. The implementation method is carried out by counseling, training and mentoring residents and farmer groups to maximize the results of empowerment. In addition, leaflets as educational tools are given as a guide. As for the steps taken: firstly, the lecturers of the agrotechnology study program to residents and farmer groups, secondly, training, starting from the selection of good planting materials. Third, assistance related to the use of household agriculture (home gardens) with horticultural crop cultivation techniques. From the series of activities to use the house yard, there are several indications of the success of the program. Among them is the attitude of residents that shows positive changes, namely an increase in the awareness of residents, the majority of whom are farmers, of the importance of using their yards for growing vegetable crops in a vertical way by participating in activities, enthusiasm of residents / farmers and awareness of the use of vegetable cultivation yards.